1986
DOI: 10.1002/jso.2930330310
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastases of nasopharyngeal carcinoma: A study of 256 male patients

Abstract: The records of 256 patients with nasopharyngeal carcinoma have been reviewed to determine the incidence and location of distant metastases. Sixty-three patients underwent autopsy. The incidence of distant metastases was 36% overall, and 51% in the autopsy patients. Bones, distant lymphnodes, liver, and lungs were the most common sites of distant metastases. Liver was the most common site in the autopsy patients. Compared to other major histological subtypes, undifferentiated carcinoma had the highest incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
111
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 20 publications
4
111
0
Order By: Relevance
“…The most common histological variant was the undifferentiated carcinoma (WHO Type III). The incidence of distant metastasis at presentation, which was 33 % in our series, is similar to world series [5]. All recurrences/ relapse were noted within 3 year of diagnosis, this was also comparable to the global data [6].…”
Section: Discussionsupporting
confidence: 90%
“…The most common histological variant was the undifferentiated carcinoma (WHO Type III). The incidence of distant metastasis at presentation, which was 33 % in our series, is similar to world series [5]. All recurrences/ relapse were noted within 3 year of diagnosis, this was also comparable to the global data [6].…”
Section: Discussionsupporting
confidence: 90%
“…This is especially true for patients who present with locally advanced disease (Ahmad and Stefani, 1986). A prospective study showed a high rate of subclinical distant metastasis, with a distinctive feature of bone marrow invasion (Micheau et al, 1987).…”
mentioning
confidence: 99%
“…It remained the major cause of death, despite the improving locoregional control. Two decades ago, a retrospective review and an autopsy study of patients with NPC has found that the overall incidence of distant metastasis was 36% [13] . In the report, liver was the most common site of involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of locoregionally advanced tumor, the use of concurrent chemoradiation was shown to be superior compared to radiotherapy alone, either in terms of improvement in local and regional control [3][4][5] , or reduced risk of distant failure [3,[6][7] . In a study involving 256 patients with NPC, the incidence of systemic metastasis was up to 36% [8] , the most common sites of which being the bones, lungs and the liver. Data on the treatment of distant failures after radiotherapy for NPC is limited.…”
Section: Introductionmentioning
confidence: 99%